REKONSTRUKSI BAYANG-BAYANG KONFLIK YANG MENYELIMUTI OLAHRAGA TENIS MEJA INDONESIA - Ramadani, Muhammad Gilang (Hanoman Journal: Physical Education and Sport, 2024)
The sport of table tennis continues to grow and has become an integralÂ part of Indonesian people's lives. In Indonesia, the sport of table tennis has become one of the most popular and popular, but along with its popularity, a number of conflicts have arisen which have hampered the development and progress of this sport. There has been a prolonged conflict since the mid-2010s which has hampered the progress of Indonesian table tennis achievements. This research aims to reconstruct the shadow of conflict that surrounds the sport of table tennis in Indonesia. The research method used is a qualitative descriptive method through literature study sourced from journals, scientific articles, books and other relevant sources. The results of this research show that the sport of table tennis in Indonesia has been characterized by various conflicts, especially in the last decade. The leadership dualism that hit PTMSI in 2018 spread to the non-participation of Indonesian table tennis athletes in the 2019 SEA Games. Indonesia did not send its athletes because of this internal chaos. Entering 2024, the shadow of conflict still hangs over the Indonesian sport of table tennis. This conflict continues to drag on, eroding the organization's foundations and hampering the progress of table tennis in Indonesia. Conflicts occur due to several root problems, such as dissatisfaction with leadership, communication gaps, unclear governance, and allegations of corruption. The impact of this conflict was not only felt by athletes and organizational administrators, but also by all table tennis enthusiasts and fans in the country.